2015
DOI: 10.3390/v8010005
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1, Immune Response and Autoimmunity

Abstract: Human T-lymphotropic virus type-1 (HTLV-1) infection is associated with adult T-cell leukemia/lymphoma (ATL). Tropical spastic paraparesis/HTLV-1-associated myelopathy (PET/HAM) is involved in the development of autoimmune diseases including Rheumatoid Arthritis (RA), Systemic Lupus Erythematosus (SLE), and Sjögren’s Syndrome (SS). The development of HTLV-1-driven autoimmunity is hypothesized to rely on molecular mimicry, because virus-like particles can trigger an inflammatory response. However, HTLV-1 modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 86 publications
(114 reference statements)
1
57
0
3
Order By: Relevance
“…This is in accordance with previous studies that had observed an immunomodulatory response in asymptomatic carriers [62, 70]. Pro-inflammatory cytokines (Th1) are involved in the progression of myelopathy and IFN-γ downregulates the production of IL-4 by Th2 cells [52,70]. We inferred that in asymptomatic individuals, immune responses were modulated to control inflammation by an increased production of IL-4 and IL-10.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with previous studies that had observed an immunomodulatory response in asymptomatic carriers [62, 70]. Pro-inflammatory cytokines (Th1) are involved in the progression of myelopathy and IFN-γ downregulates the production of IL-4 by Th2 cells [52,70]. We inferred that in asymptomatic individuals, immune responses were modulated to control inflammation by an increased production of IL-4 and IL-10.…”
Section: Discussionsupporting
confidence: 92%
“…HAM/TSP progression is associated with the HTLV-1 PVL and with an increase in pro-inflammatory cytokines, such as IFN-γ, TNF-α, IL-2, and IL-6 [45,4852]. The analysis of serum IL-10 demonstrated a higher concentration in patients infected with HTLV-1 (HAM/TSP and ACs) than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that overexpression of the natural p53 inhibitory protein mouse double minute 2 homolog (MDM2) or expression of certain viral proteins upon viral infection, such as human papillomavirus (HPV) E6 and human T-lymphotropic virus 1 (HLTV-1), also lead to inhibition of p53 activity, which has been linked to tumorigenesis [81,82,83,84]. Interestingly, HTLV-1 infection appears to be associated with increased development of autoimmune diseases, including RA, SS, and systemic lupus erythematosus (SLE) [85], although it is yet to be determined whether this HTLV-1-induced chronic inflammation is at least partially resulted by p53 dysfunction in immune cells.…”
Section: Trp53 Dysfunction and Inflammation—the Non-canonical And mentioning
confidence: 99%
“…A diferencia de lo que ocurre en HIV que destruye los linfocitos CD4, HTLV-1 promueve la proliferación de estas células así como linfocitos CD8 y células NK (19) alterando la función de los linfocitos CD4 a través de una serie de factores de transcripción como la proteína TAX, FOXP3 y el factor nuclear de células T activadas (NFAT), con el desarrollo de respuesta inmune deficiente y autoinmunidad (20).…”
Section: Ventosilla R Y Colunclassified